TINJAUAN HUKUM ISLAM TENTANG CRYPTOCURRENCY: STUDI KASUS BITCOIN DALAM KATEGORI HARTA SYUBHAT - Muhammad Ridha (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to analyze the legal status of Bitcoin from the perspective of Islamic law, focusing on the fatwa of the Indonesian Ulema Council (MUI), its classification as a syubhat property, and its fakyif fiqh. Bitcoin, as a leading cryptocurrency, poses a unique challenge to Islamic financial principles due to its decentralized nature and high volatility. This analysis highlights the core issues of gharar (uncertainty) and maisir (speculation/gambling) arising from the absence of a clear underlying asset and extreme fluctuations in value. The DSN-MUI fatwa expressly prohibits the use of cryptocurrencies as a currency, but allows them as commodities on the condition that they have clear underlying assets and real benefits. This position shows the complexity of valuing modern financial instruments. Bitcoin's absence of underlying assets and extreme volatility make it ineligible as a sharia-legal commodity, thus placing it in the category of shubhat property. This research provides understanding for Muslim investors facing complex modern financial instruments. Keywords: Bitcoin, Cryptocurrency, Islamic Law, MUI Fatwa, Syubhat Property, Gharar, Maisir, Takyif Fiqih.